Colored Compomers in Pediatric Dentistry Practice: Can Personality Profile, Parenting Style and Socioeconomic Factors Influence Preference? - Fernanda Vieira Belém; Cristiane Baccin Bendo; Marco Aurélio Benini Paschoal (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To investigate the preference of parents/caregivers and their children regarding using colored compomer (Twinky Star®, Voco, Germany) as a restorative option and factors associated with its choice. Material and Methods: A dental mannequin containing colored compomers and traditional materials (composite resin, glass ionomer cement, and amalgam) was presented to 260 pairs of adults and children aged 5-11 years, who were examined for dental caries to verify the preference of dental materials in two public health services. The parenting style and child personality profiles were assessed. Bivariate analysis and Poisson regression were performed. Results: Most adults (74.2%) preferred traditional materials, and family income (p=0.001) and educational level (p<0.001) were associated with this choice. Age up to 7 (p<0.001) was a variable associated with children's choice of colored restorations (72.3%). Children younger than seven years old showed a prevalence of choosing colored compomers 1.20 times higher than their older counterparts. In contrast, adults with children younger than seven years old and less than 11 years of education presented 1.74 and 2.17 higher prevalence of choosing colored compomers, respectively. Conclusion: Caregivers with higher educational levels showed more excellent resistance to colored restorations, and children younger than seven years old had better acceptance of the material with playful proposals.